Lifestyle of women with neoplastic disease. Part II. Dietary habits and physical activity of women with neoplastic disease - Szymańska, Jolanta; Pietryka-Michałowska, Elżbieta; Jurkowska, Barbara (Polish Journal of Public Health, 2010)
Introduction. Dietary habits suitable for nutritional requirements of human organism together with everyday physical activity are likely to maintain or improve the basic health potential and reduce the risk of neoplasms. Cancer induces a variety of changes in the life of the affected individuals and their families. The objective of the present study was to assess whether cancer influenced the dietary habits and physical activity of the affected women.Material and methods. The study comprised 331 women diagnosed with neoplastic diseases. The research tool was the questionnaire designed by the authors. The questionnaire was distributed amongst women attending prophylactic examinations at the hospital outpatient clinic (Teaching Hospital No. 4) between March 2007 and April 2009.Results. The study findings demonstrated that cancer significantly affected dietary habits and leisure activities. Women more eagerly and more frequently socialize and prefer active leisure pursuits. Moreover, they pay closer attention to the diet as they feel responsible for the health of family members. The respondents are disciplined, compliant with doctor’s orders, and full of confidence in the medical personnel, which is extremely important for the treatment process and its outcomes.